2008
DOI: 10.1007/s11999-007-0089-z
|View full text |Cite
|
Sign up to set email alerts
|

CT Scan Method Accurately Assesses Humeral Head Retroversion

Abstract: Humeral head retroversion is not well described with the literature controversial regarding accuracy of measurement methods and ranges of normal values. We therefore determined normal humeral head retroversion and assessed the measurement methods. We measured retroversion in 65 cadaveric humeri, including 52 paired specimens, using four methods: radiographic, computed tomography (CT) scan, computer-assisted, and direct methods. We also assessed the distance between the humeral head central axis and the bicipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 46 publications
(109 reference statements)
3
65
0
1
Order By: Relevance
“…Methods of measurement have included direct anatomic [13,15], radiographic [4,14], ultrasound [10], computed tomography scan [3,8], MRI [6], and computer-assisted methods [5,19,21,22]. Boileau et al [2] showed that the radiographic method overestimated the humeral head retroversion relative to the computer-assisted method. However, there was no difference between humeral head retroversion obtained by the CT scan method, the direct method, and the computer-assisted method.…”
Section: Discussionmentioning
confidence: 99%
“…Methods of measurement have included direct anatomic [13,15], radiographic [4,14], ultrasound [10], computed tomography scan [3,8], MRI [6], and computer-assisted methods [5,19,21,22]. Boileau et al [2] showed that the radiographic method overestimated the humeral head retroversion relative to the computer-assisted method. However, there was no difference between humeral head retroversion obtained by the CT scan method, the direct method, and the computer-assisted method.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, reestablishing normal retroversion is essential when implanting a humeral prosthesis for any indication, but particularly in fractures of the proximal humerus [1,2,7,[11][12][13]. Correct retroversion of the humeral component is important because it affects the position of the instant center of rotation [1,2,14], the stability of the joint [9], and the amount of external rotation [15].…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy and reliability of the methods used in the present study cannot of course be compared to methods using sophisticated instruments and complex computer-assisted three dimensional reconstructions. [12,13,25] Also the accuracy of the present study could have been improved if an image analysis program such as NIH Image or ImageJ had been used.…”
Section: Limitations Of the Present Studymentioning
confidence: 99%
“…[l,5,8,10-13] However, not many studies have analyzed the reliability and repeatability of the method. [12,13,21,25] The most commonly used measure of the magnitude of error associated with a certain measurements is the TEM, which is the square root of the measurement error variance. [29] It is expressed in the same unit of measurement as used in the original measurement.…”
Section: Intra-and Inter-observer Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation